Mediating role of job satisfaction on reward system and training and development towards employees retention in the banking sector of Yemen - Al-Razehi, Hareth Abd Al-Wareth
Commercial banks in Yemen face many challenges, especially when it comes to retaining employees. Many employees give up their jobs in commercial banks in Yemen due to several factors. The most important factor is the deterioration and weakness of thebank's reward system and their lack of interest in training and development programmes. These problems might affect banks' productivity, which may be due to ineffective human resource strategies. The ability to link employee satisfaction with employee retention is critical in determining employee satisfaction on the organisation's overall performance. Therefore, this study aims to determine the effect of reward system and training and development on employee retention, which mediates by job satisfaction in Yemen's commercial banks. Data were collected from the headquarters of 15 commercial banks operating in Yemen using simple random sampling. A set of questionnaires with 5-point Likert scale was distributed to employees in the headquarters in Yemen. The questionnaire was modified to fit the context of the study. After the pretest presented to experts and specialists, a pilot study was conducted. The data were analysed using Structural Equation Modelling (SEM) by IBM SPSS AMOS 22.0. The results indicate that reward system and training and development have a statistically significant effect on job satisfaction, while employee satisfaction has a significant positive effect on employee retention in Yemen's banking sector. In contrast, training and development have no statistically significant effect on employee retention in Yemen's banking sector. The results show that the job satisfaction plays the role of partial mediation between reward system and employee retention, while it plays the role of full mediation between training and development and employee retention. It is a complete mediation because the direct impact is not significant. This indicates that employee satisfaction is an important variable that links reward system and training and development to employee retention in Yemen's banking sector. This study made significant theoretical, practical, and methodological contributions in this research field by developing a model of the effect of reward system and training and development on employee retention in job satisfaction and employee retention. This model can assist policymakers in developing and implementing human resource practices.